Hunt and his Friends - Hay, Daisy (Romanticism and Victorianism on the Net, 2011)
This essay reads Hunt’s Foliage alongside works by three members of his circle: John Keats, Elizabeth Kent and Mary Novello. It argues that the work of all three is inflected by Foliage and Hunt’s philosophy of sociability, and it suggests that Hunt himself is not diminished when his work is contextualised by that of his friends. Rather, friendship is so central to his sociable aesthetic that we diminish his achievements when, in an attempt to free him from the shadows cast by his contemporaries, we critically render him in isolation. It represents Hunt as a man who was made by his friends, and whose friends were made by him.